2013
DOI: 10.1016/j.yexcr.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Inherent phenotypic plasticity facilitates progression of head and neck cancer: Endotheliod characteristics enable angiogenesis and invasion

Abstract: The presence of the EMT (epithelial-mesenchymal transition), EndMT (endothelial-mesenchymal transition) and VM (vasculogenic mimicry) demonstrates the multidirectional extent of phenotypic plasticity in cancers. Previous findings demonstrating the crosstalk between head and neck squamous cell carcinoma (HNSCC) and vascular endothelial growth factor (VEGF) imply that HNSCC cells share some functional commonalities with endothelial cells. Our current results reveal that cultured HNSCC cells not only possess endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…Similar to our previous ATCC OSCC cell characterization studies [17], JSCC1, JSCC2 and JSCC3 cell cultures uniformly demonstrated strong cytokeratin staining along with coexpression of cytokeratin and vimentin in cellular subpopulations (Supplemental Figure S1). …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to our previous ATCC OSCC cell characterization studies [17], JSCC1, JSCC2 and JSCC3 cell cultures uniformly demonstrated strong cytokeratin staining along with coexpression of cytokeratin and vimentin in cellular subpopulations (Supplemental Figure S1). …”
Section: Resultssupporting
confidence: 87%
“…Formalin fixed cells were incubated with vimentin (1:200, Abcam, Cambridge, MA) or a pancytokeratin cocktail (AE1/AE3 + 5D3, 1:100, Abcam,) antibodies, followed by incubation with FITC or Texas Red conjugated secondary antibodies (Abcam, Cambridge, MA) [17]. Nuclei were stained with 4′,6′-Diaminidino-2-phenylindole dihydrochloride (DAPI, Abcam).…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxia was also reported to promote VM through other signaling pathways, such as the extravascular VE-cadherin and its role in the acquisition of the VM phenotype [46]. In addition, the multi-phenotypic reciprocity, observed in VM-forming cancer cells, has the capacity to facilitate tumor progression and metastasis [47,48]. Because of such a phenotypic switch, the VM-forming ELC are different from normal endothelial cells, rendering the VM channels inherently resistant to conventional anti-angiogenic therapy [32,49].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tumor cell mobility and invasiveness were heightened. 34 In non–small cell lung cancer, Dickkopf-1 significantly induces VM formation and promotes cancer cell growth, migration, and metastasis via overexpression of EMT- and CSC-associated proteins. 35 Maspin has a positive correlation with VM; deregulated maspin facilitates tumor cell invasion and metastasis in non–small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%